(untitled) (Los Angeles, CA, 2008)
This book provides an overview of metadata--its types, roles, and characteristics; a discussion of metadata as it relates to resources on the Web; a description of methods, tools, standards, and protocols that can be used to publish and disseminate digital collections; and a handy glossary. The book also has an essay on the importance of standards-based rights metadata to the activities of cultural institutions; and a section entitled "Practical Principles for Metadata Creation and Maintenance."
Keywords: Metadata,Database management,Information organization,Siêu dữ liệu,Quản trị cơ sở dữ liệu,Tổ chức thông tin